Inducing heterogeneity in an austenitic stainless steel by equal channel angular sheet extrusion (ECASE) - Muñoz Bolaños, Jairo Alberto (2019)
An austenitic stainless steel was processed at room temperature by equal channel angular sheet extrusion (ECASE). The microstructure evolution was heterogeneous across the sheet thickness with a higher martensitic transformation in the zones closer to the edges than in the sheet core due to the deformation-induced martensite (DIM) phenomena. The material heterogeneity induced by one ECASE pass gave a good strength-ductility relationship.